A case study of the effect of cladding panels on the response of reinforced concrete frames subjected to distant blast loadings - Li, Bing (2012)
The turbine building is a vital structure within nuclear power plants that houses turbines, moisture separators and electric generators among other important equipment. Turbine buildings are typically frame structures that in most cases have not been designed to resist blast loadings. The authors to determine